2013
DOI: 10.1177/1528083713516663
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three body abrasive wear behavior of bidirectional jute fiber reinforced epoxy composites

Abstract: The need of eco-friendly, sustainable, and biodegradable material for structural and nonstructural application increases day by day. Jute fiber is one of the largely produced natural fibers and has properties comparable to synthetic fibers. Currently, abrasive wear of the agricultural and engineering machine components is one of the major industrial problems. An attempt has been made in this paper to study the abrasive wear behavior of bidirectional jute fiber-epoxy composites. Composites of five different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The main aim of this study was to characterize the morphology of abraded surfaces and to recognize the mode of material removal. SEM observations reported previously reveal that the abrasive wear of the polymer composites in particular is a complex process involving matrix micro‐cracking, ploughing, micro‐cutting, fiber breakage, and so on .…”
Section: Resultsmentioning
confidence: 94%
“…The main aim of this study was to characterize the morphology of abraded surfaces and to recognize the mode of material removal. SEM observations reported previously reveal that the abrasive wear of the polymer composites in particular is a complex process involving matrix micro‐cracking, ploughing, micro‐cutting, fiber breakage, and so on .…”
Section: Resultsmentioning
confidence: 94%
“…Figure 10 shows the variation of specific wear rate with normal load under steady-state conditions for TiO 2 -and ZnOfilled E-glass fibre-polyester composites at sliding speed of 0.5 m s −1 and figure 11 shows same at sliding speed 1.0 m s −1 . It is observed that specific wear rate increases with increase in the load [35]. The unfilled composite exhibits highest wear rate for all load conditions for each sliding Figure 12 shows the variation of specific wear rate with sliding distance under steady-state conditions for TiO 2 -and ZnO-filled E-glass fibre-polyester composites at normal load of 4 N. Figure 13 shows same at normal load of 12 N. It is found that at small sliding distance, unfilled E-glass fibrereinforced composites exhibit highest specific wear rate and the same phenomenon is shown among all the sliding distances.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…[1,2] Among these materials, jute fibers (JF) have attracted considerable attention for the fabrication of fiber-reinforced composites. [3][4][5][6][7] A plethora of reports are available in the literature on JF-reinforced polymers and their properties. Dilfi et al [3] investigated the influence of fiber surface modification on the mechanical behavior of JF-reinforced epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Raghavendra et al [4] compared the tribological properties of epoxy composites reinforced with jute and glass fibers and showed that the jute fiber/epoxy specimens had superior properties than glass-reinforced epoxy composites. Militky et al [5] explored the creep behavior of treated JF/epoxy (EP) composites. It was shown that the treated composites had less creep strain than untreated one at all temperatures.…”
Section: Introductionmentioning
confidence: 99%